Genome-wide identification, characterization and expression of HSP 20 gene family in dove - Hou, Zhe; Li, Ang; Huang, Changbing (Frontiers in Genetics, 2022)
Abstract: Davidia involucrata is a significant living fossil with high abiotic stress tolerance. Although heat shock protein 20 (HSP20) has already been linked to heat stress, nothing is known about HSP20 family protein activities in D. involucrata. The functional dynamics of the D. involucrata HSP20 (DiHSP20) gene family were identified and characterized using a thorough genome-wide investigation. From the genome of D. involucrata, a total of 42 HSP20 genes were discovered, distributed across 16 chromosomes. The DiHSP20 proteins were divided into seven separate subfamilies by our phylogenetic analysis, which was validated by the conserved motif composition and gene structure studies. Segmental duplication events were shown to play a crucial role in the expansion of the DiHSP20 gene family. Synteny analysis revealed that 19 DiHSP20 genes of D. involucrata shared a syntenic connection with Arabidopsis genes, 39 with C. acuminata genes, and just 6 with O. sativa genes. Additionally, heat stress differently enhanced the expression levels of D. involucrata HSP20 genes. After one hour of heat treatment, the expression levels of most DiHSP20 genes, particularly DiHSP20-7, DiHSP20-29, DiHSP20-30, DiHSP20-32, and DiHSP20-34, were dramatically increased, suggesting that they might be employed as heat tolerance candidate genes. Overall, these findings add to our knowledge of the HSP20 family genes and provide helpful information for breeding heat stress resistance in D. involucrata.